The Cassava NBS-LRR Genes Confer Resistance to Cassava Bacterial Blight - Zhang, He; Ye, Zi; Liu, Zhixin; Sun, Yu; Li, Xinyu; Wu, Jiao; Zhou, Guangzhen; Wan, Yinglang (Frontiers in Plant Science, 2022)
Cassava bacterial blight (CBB) caused by Xanthomonas axonopodis pv. manihotis (Xam) seriously affects cassava yield. Genes encoding nucleotide-binding site (NBS) and leucine-rich repeat (LRR) domains are among the most important disease resistance genes in plants that are specifically involved in the response to diverse pathogens. However, the in vivo roles of NBS-LRR remain unclear in cassava (Manihot esculenta). In this study, we isolated four MeLRR genes and assessed their expression under salicylic acid (SA) treatment and Xam inoculation. Four MeLRR genes positively regulate cassava disease general resistance against Xam via virus-induced gene silencing (VIGS) and transient overexpression. During cassava-Xam interaction, MeLRRs positively regulated endogenous SA and reactive oxygen species (ROS) accumulation and pathogenesis-related gene 1 (PR1) transcripts. Additionally, we revealed that MeLRRs positively regulated disease resistance in Arabidopsis. These pathogenic microorganisms include Pseudomonas syringae pv. tomato, Alternaria brassicicola, and Botrytis cinerea. Our findings shed light on the molecular mechanism underlying the regulation of cassava resistance against Xam inoculation.